Genera of the parasitoid wasp family Monomachidae (Hymenoptera: Diaprioidea) - Johnson, Norman F.; Musetti, Luciana (Zootaxa, 2012)
The genera of the family Monomachidae are revised. Chasca Johnson & Musetti, new genus, is described, with two species:Chasca andina Musetti & Johnson, new species (type species, Chile) and C. gravis Musetti & Johnson, new species (Peru).The genus Tetraconus Szépligeti is treated as a junior synonym of Monomachus Klug (new synonymy), and its type species istransferred to Monomachus as M. mocsaryi (Szépligeti), new combination A phylogenetic analysis places Chasca and Mono-machus as sister-groups; within Monomachus, the three species of Australia and two species of New Guinea are basal, and the radiation of 21 species in tropical America and Valdivia is recovered as a monophyletic group.